Interruption of Sneddon-Wilkinson Subcorneal Pustulation with Infliximab - Lorenz Kretschmer; Julia-Tatjana Maul; Thomas Hofer; Alexander A. Navarini (Karger Publishers, 2017)
Subcorneal pustular dermatosis (SCPD, Sneddon-Wilkinson disease) is a rare chronic-relapsing skin disorder that typically manifests as flaccid sterile pustules without systemic symptoms. Although the accumulation of neutrophils is acknowledged to be a hallmark of SCPD, its exact pathomechanism is still not known. Several chemotactic factors have been implicated in neutrophil recruitment and invasion, including the proinflammatory cytokine TNF-α. These findings correspond well with clinical reports of successful off-label use of TNF blocking agents in cases that were refractory to first-line therapy, mostly with dapsone. We report the case of a 29-year-old male with atypical and severe manifestation of SCPD that resolved after a single dose of infliximab. Consolidation was observed 1 day after treatment and regression of skin lesions occurred after a few days. Residual scarring and postlesional hyperpigmentation was seen at a 2-month follow-up appointment. The patient was initiated on a daily maintenance therapy with dapsone, which led to a drop in hemoglobin and had to be stopped. Upon development of small, scaly lesions, a maintenance therapy with infliximab was started and the patient has had no recurrence to date. Anti-TNF agents present a promising option for patients affected by severe SCPD. We review the reports of similar cases in the literature to date.